2021
DOI: 10.1002/asia.202100126
|View full text |Cite
|
Sign up to set email alerts
|

Selective Lithium Adsorption of Silicon Oxide Coated Lithium Aluminum Layered Double Hydroxide Nanocrystals and Their Regeneration

Abstract: Silicon oxide-coated lithium aluminum layered double hydroxide (Li x Al 2 -LDH@SiO 2 ) nanocrystals (NCs) are investigated to selectively separate lithium cations in aqueous lithium resources. We directly synthesized Li x Al 2 -LDH NC arrays by oxidation of aluminum foil substrate under a urea and lithium solution. Various lithium salts, including Cl À , CO 3 2À , NO 3 À , and SO 4 2À , were applied in aqueous solution to confirm the anion effect on the captured and released lithium quantity of the Li x Al 2 -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…When Fe(III) was doped into Li/Al-LDHs, it would enhance the stability of Li/Al-LDHs and reduce its solubility in nanocomposites [26]. The Li x Al 2 -LDH adsorbents were prepared by Lee et al [27]. The Li x Al 2 -LDH@SiO 2 nanostructure showed enhanced Li + adsorption performance and high Li + selectivity in mixed water resources of Mg 2+ , Na + , and K + cations.…”
Section: Introductionmentioning
confidence: 99%
“…When Fe(III) was doped into Li/Al-LDHs, it would enhance the stability of Li/Al-LDHs and reduce its solubility in nanocomposites [26]. The Li x Al 2 -LDH adsorbents were prepared by Lee et al [27]. The Li x Al 2 -LDH@SiO 2 nanostructure showed enhanced Li + adsorption performance and high Li + selectivity in mixed water resources of Mg 2+ , Na + , and K + cations.…”
Section: Introductionmentioning
confidence: 99%
“…Adsorption is the most promising strategy for recovering Li from aqueous resources because it is more climate-friendly and more effective in an industrial application . Although there are many studies reported in the literature regarding metal ion extraction based on different functionalized composite materials, aluminum hydroxides (AlOH), , aluminum oxides (AlO x ), manganese oxides (MnO x ), and titanium oxides (TiO x ) , have been known to be the most selective lithium adsorbents until now. They are classified as inorganic crystalline solids either being studied for direct lithium extraction from brines or employed as cathode materials in lithium-ion batteries.…”
Section: Introductionmentioning
confidence: 99%